Changes in Pediatric Trauma During the COVID-19 Pandemic; Does the Pandemic Have an Effect on the Severity of Traumas? - Dilnur Sevinç; Aslıhan Nallı; Bade Toker Kurtmen; Emine Burcu Çığşar Kuzu; Mustafa Onur Öztan (Journal of Pediatric Research, 2023)

(untitled)
Aim:Traumas are the most common cause of mortality and morbidity in children. Coronavirus disease-2019 (COVID-19) was shown to affect pediatric mental health, child neglect, and the occurrence of traumatic injuries. This study aimed to characterize pediatric trauma cases presenting to our institution before and after the pandemic began.Materials and Methods:Patients with trauma who were admitted to our emergency department between March, 2019 and March, 2021 were included. The patients were classified into two groups as before and after the pandemic began (March, 2020). Trauma characteristics, the severity of the injury, and prognosis were assessed. The patients’ injury severity scores (ISS) and pediatric trauma scores (PTS) were noted.Results:A total of 1,718 patients were included in this study. The number of pediatric trauma admissions dropped from 1,039 to 679 after the pandemic started. There was no difference between these groups in terms of age (p=0.874) or gender (p=0.106). There was a significant decrease in the number of traumatic injuries (p<0.001) especially during the first shutdown period (April, May, and June, 2020. Additionally, there was a significant increase in terms of foreign body aspiration (p=0.001) and pedestrian injuries (p=0.016). Although a significant increase was noted in the ISS of the patients (p<0.001), no differences were found between the PTSs (p=0.075) or multi-organ injuries (p=1.000). Also, no significant differences were observed regarding mortality (p=0.650), household accidents (p=0.600), trauma type (p=0.533), the need for transfusion (p=0.166), surgery (p=0.077) or mechanical ventilation (p=0.464) between the two groups.Conclusion:The COVID-19 pandemic altered social patterns, leading to a decrease in pediatric traumas. This decrease was most prominent during the shutdown period. The variables showing severe trauma, such as the need for surgery, did not change despite a significant increase in ISS. This was attributed to a decrease in admissions for minor trauma.